1982
DOI: 10.1302/0301-620x.64b2.6978339
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of fibrous non-union of fractures by pulsing electromagnetic stimulation

Abstract: Fifty-three ununited fractures with a median time since injury of28 months were treated by electrical stimulation using pulsing electromagnetic fields. Union was achieved in 38 cases (71.7 per cent) in a median time ofsix months. For ununited fractures ofthe tibia the success rate was higher at 86.7 per cent. Previous or active sepsis, the presence of plates or nails, the age of the patient or the time since the injury did not affect the results. Analysis ofthe failures suggests that inadequate immobilisation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(35 citation statements)
references
References 11 publications
0
33
0
2
Order By: Relevance
“…The use of specific electromagnetic fields for the treatment of nonunions is well known [2,14,20]. The union rates of ununited fractures treated with pulsed electromagnetic fields (PEMF) are greater than 80% [1,11,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of specific electromagnetic fields for the treatment of nonunions is well known [2,14,20]. The union rates of ununited fractures treated with pulsed electromagnetic fields (PEMF) are greater than 80% [1,11,20].…”
Section: Introductionmentioning
confidence: 99%
“…The union rates of ununited fractures treated with pulsed electromagnetic fields (PEMF) are greater than 80% [1,11,20]. Originally, the use of electricity to stimulate osteogenesis was based on the idea of simulating the natural endogenous streaming potentials in bone with microampere currents applied directly via electrodes or induced by external electromagnetic fields [3].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with most other reports, we have found that nonunions of the tibia are most likely to heal, while nonunions of the humerus remain problematic. All four of our nonunions of the humerus were very mobile, although none of them had a fracture gap exceeding half the diameter of the bone, a crucial distance according to many authors (Brighton et al 1981, Sharrard et al 1982. Neither did they show signs of synovial pseudarthrosis on bone scintigraphy.…”
Section: Discussionmentioning
confidence: 62%
“…The results in this series cannot compete with those of bone graft surgery for nonunions. Although it has not yet been possible to explain the exact mechanism by which electricity may enhance bone-healing, numerous reports have already been published concerning electrical treatment of fractures and nonunions (Jorgensen 1972, Bassett et al 1978, Zichner & Happel 1979, De Haas et al 1980, Khasigian 1980, Sharrard et al 1982.…”
Section: Electrical Treatment Of Non-united Fracturesmentioning
confidence: 99%
“…One that is induced to produce bone (IOPC) and the other that is determined to produce bone (DOPC). The former (IOPC) exists in all connective tissue and the latter (DOPC) is found only in the marrow 5 . Because the bone marrow is the only tissue that contains in abundance, both determined and inducible osteoprogenitor cells, it is the logical graft of choice 6 .…”
Section: Introductionmentioning
confidence: 99%